Linguistic Competency Analysis of Consecutive Interpreting Results for 6th Semester Students of FKIP UMSU - Bambang Panca Syahputra; Yusni Khairul Amri; Rakhmat Wahyudin Sagala (Budapest International Research and Critics University, 2021)
One of the problems in learning Translation, students encounter inscrutability of language or the translator's ignorance of the speech delivered. However, this vagueness is not a limitation but a feasible thing because the consecutive process occurs quickly. This study aimed to describe the quality (validity, efficacy, and practicality) of an Indonesian Qualification Framework (IQF-based) translated textbook using the Consecutive Interpretation Model. It is designing an (IQF-based) translated textbook using the Consecutive Interpretation Model. The Consecutive Interpretation Model was used to create an (IQF-based) translated textbook. This study triggered by two factors: (1) Students performed a limited ability to communicate in English orally, and (2) IQF is in high demand among university graduates. This study employed a research and development design. A five-step analysis was obtained based on Plomp's (1997) approach, including the investigation, design, realization, test, evaluation, revision, and implementation phases. The subject was undergraduate students enrolled in Translation course at the Faculty of Teacher Training and Education, Universitas Muhammadiyah Sumatera Utara. The Consecutive Interpreting method involves 40 students of the English Education Study Program by applying interpreting techniques to language interpreters with various genres. The result indicates that consecutive interpreting has successfully enhanced students' performance; students rapidly create thoughts or facts.